Retour d’expérience post pandémie suite à la généralisation de l’enseignement/apprentissage à distance. Un moyen de penser la formation des enseignants et le fonctionnement de l’université de demain - Fatima Zohra Sakrane; Denis Legros (Multilinguales)
The world has been deeply affected by the global Coronavirus pandemic. In addition to global public health problems, all economic and social sectors have been disrupted and millions of people threatened in their equilibrium and well-being. School and university communities were the first to be affected and had to adapt as a matter of urgency. The algeriangovernmentdecided on March 22, 2020 to close schools and universities. A directive from the Ministry of Higher Education and Scientific Research has been sent to university officials asking them to adopt online platforms to ensure "pedagogical continuity". To reliably and efficiently manage these new teaching / learning modalities, university managers had to mobilize all available human resources, teaching staff, administrative and technical staff, to maintain the continuity of teaching and learning. This need, which became evident from the start of the pandemic, revealed the many shortcomings in terms of resources. Teachers, the main players, had to take advantage of existing means to face this challenge. The experience feedback that we wish to share in the context of this article concerns the implementation and generalization of online education in the Algerian university context and its effects on learning. This experience allowed us to become aware of the didactic and pedagogical upheavals caused by the introduction of ICT and digital tools during distance teaching / learning of French and French in FLE.